Early Results of Inguinal Hernia Repair under General Anesthesia and a One-Day Surgery Protocol - Arunnart, Methas (The Thai Journal of Surgery, 2022)
Objective: Several studies have shown that herniorrhaphy under general anesthesia (GA) could be done in a one-day surgery (ODS) setting. However, no studies have evaluated the outcomes and complications of this approach. We aim to evaluate the early outcomes of herniorrhaphy under GA in a ODS protocol. Methods: Medical charts of patients who underwent herniorrhaphy between the years 2018 and 2022 were reviewed. Data on patient characteristics and early outcomes were collected. Patients with ASA class ≥ III, acute incarcerated hernia, strangulated hernia, and who did not have a good care provider were excluded. Results: 100 patients underwent herniorrhaphy under GA in a ODS protocol. All patients were male. More than 50% of patients were between 41 to 60 years of age. The majority (71%) of cases had ASA class I. The average overall length of stay ± SD was 6.1 ± 0.3 hours. Seven patients could not be discharged home on the same day due to urinary retention, surgeon’s concern, severe postoperative pain, and dyspnea. The average length of stay in patients who needed post-operative admission was 21.6 ± 6.5 hours. The overall complication rate was 9%. Urinary retention was the main complication and the main cause of postoperative admission. There were no deaths, readmissions, or early recurrent inguinal hernia. Conclusion: Herniorrhaphy under GA was effective and safe and could be done within a ODS setting. The rate of complication was low. Urinary retention was the main complication causing failure to discharge on the same day. However, these complications were not a serious problem and patients could usually be discharged the next day.